Implementation of the Political Marketing Mix and Electronic Word of Mouth in the 2024 Regional Head Election of Karawang Regency - Setiawan, Naufal Alip Putra; Ali, Mochammad Mukti; Sofiati, Nunung Ayu; Ismail, Gurawan Dayona; Sakti, Anggono Raras Tirto (Green Publisher Indonesia, 2026)
This study aims to analyze the influence of the Political Marketing Mix on Electronic Word-of-Mouth (E-WoM) and Voting Decision, as well as the mediating role of E-WoM in the 2024 Regional Head Election of Karawang Regency. The research adopts a quantitative approach using Structural Equation Modeling (SEM) with SmartPLS 4.1.1.4. Data were collected from 200 respondents who participated in the 2024 Karawang local election through an online questionnaire using a five-point Likert scale. The findings indicate that most elements of the political marketing mix product, price, place, promotion, people, and process have a positive and significant effect on E-WoM, while physical evidence does not show a significant influence. Furthermore, all elements of the political marketing mix positively and significantly affect voting decision. E-WoM is proven to have a direct positive effect on voting decision and serves as a mediating variable that strengthens the relationship between most political marketing mix elements and voting decision, except for physical evidence. These results demonstrate that voter behavior is shaped by a complex interaction of rational, emotional, and social factors, and highlight the strategic importance of digital communication and peer-to-peer information sharing in modern political campaigns. The study contributes theoretically to the development of political marketing literature in local democratic contexts and provides practical insights for political actors in designing more effective and participatory campaign strategies in the digital era.